Linguistic Borrowing and Cultural Significance : Analysing the Impact of Dholuo Figures of Speech on Olusuba Folksongs and Abasuba Cultural Identity - Otundo, Billian; Sande, Walter; Institute of African Studies (University of Bayreuth African Studies Working Papers, 2024)
This article discusses the dynamic interplay between language contact, cultural exchange, and expressive forms of communication within the multicultural societies of Abasuba and Luo living in Kenya. From a socio-pragmatic perspective of signification of figures of speech in Olusuba traditional folksongs, we elaborate on a social context that manifests and inducts the socio-pragmatics of linguistic borrowing, particularly figures of speech (FOS), from Dholuo into Olusuba traditional folksongs. Unique to this study is that in the Olusuba speech communities, speakers are found to communicate non-literally to convey ideas and/or knowledge borrowed from the Luo community. The analysis was grounded in the Semiotic Theory (Barthes 1983) and constructed around de Saussure’s Theory of Meaning (1916) which proposes that language is a union of signs whose relation between their physical and symbolic distinction is arbitrary and thus attains its meaningfulness through the rules of convention. An ethnographic research design was adopted and a qualitative analysis of linguistic features and thematic content in Olusuba folksongs was employed to examine how borrowed FOS contribute to the expressive power and cultural significance of these songs, particularly in conveying themes related to nature and socio-economic activities shared by the Abasuba and Luo communities. Additionally, the study investigates the broader implications of integrating borrowed FOS into Olusuba folksongs on the preservation and evolution of cultural identity among the Abasuba people. In this endeavour, intact cultural groups of Abasuba people in natural settings were interviewed on Dholuo-oriented Olusuba folksongs alongside non-participatory observation during the performance of the folksongs. The results, for example, revealed the use of linguistic symbols whose semantics have been induced by Olusuba-Dholuo contact. This research sheds light on the intricate relationship between language contact, cultural exchange, and identity formation in multicultural societies, offering insights into the complexities of linguistic and cultural dynamics in diverse communities.
Keywords: figures of speech; folksongs; language contact; linguistic dynamics; Olusuba-Dholuo; cultural exchange; Cultural Identity; Kenia; Luo; Abasuba; semiotic theory; theory of meaning; Ecolinguistics